2021
DOI: 10.1016/j.cmpbup.2021.100010
|View full text |Cite
|
Sign up to set email alerts
|

Use and validation of text mining and cluster algorithms to derive insights from Corona Virus Disease-2019 (COVID-19) medical literature

Abstract: The emergence of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) late last year has not only led to the world-wide coronavirus disease 2019 (COVID-19) pandemic but also a deluge of biomedical literature. Following the release of the COVID-19 open research dataset (CORD-19) comprising over 200,000 scholarly articles, we a multi-disciplinary team of data scientists, clinicians, medical researchers and software engineers developed an innovative natural language processing (NLP) platform that comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…The emergence of the COVID-19 pandemic has resulted in several studies and papers outlining the utility of AI in tackling various aspects of the disease like diagnosis, treatment, and surveillance [16][17][18][19] The number of AI papers published either as pre-print or peerreviewed has been unprecedented, even leading to the development of AI applications to keep up with and summarise the findings for scientists [20]. Some recent reviews have outlined how most of these studies or the AI applications presented in these studies have shown minimal value for clinical care [7,21].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of the COVID-19 pandemic has resulted in several studies and papers outlining the utility of AI in tackling various aspects of the disease like diagnosis, treatment, and surveillance [16][17][18][19] The number of AI papers published either as pre-print or peerreviewed has been unprecedented, even leading to the development of AI applications to keep up with and summarise the findings for scientists [20]. Some recent reviews have outlined how most of these studies or the AI applications presented in these studies have shown minimal value for clinical care [7,21].…”
Section: Introductionmentioning
confidence: 99%
“…Text mining facilitates information extraction, categorisation, grouping, trend analysis and visualisation 7 . The goal is to focus information searches to remove noise 8 and to identify hidden knowledge in the literature 9 . Zengul et al used text mining to classify literature from the NIH COVID-19 Portfolio.…”
Section: Introductionmentioning
confidence: 99%
“…developed a biomedical platform to collect data on COVID-19 clinical risks. The use of this platform revealed the difficulty of extracting relevant clinical information through text mining and the need for feedback from experts in the field to obtain reliable results 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Teir experiments yielded an accuracy of 93% to 95%, which was higher than that of other techniques used in the study. In another study, Reddy et al [22] applied an NLP algorithm to segment a collection of medical publications. Te methodology involved segmenting all the words and the associated information.…”
Section: Introductionmentioning
confidence: 99%